Diagnostic yield and clinical impact of exome sequencing in early-onset scoliosis (EOS). - Zhao, Sen; Zhang, Yuanqiang; Chen, Weisheng; Li, Weiyu; Wang, Shengru; Wang, Lianlei; Zhao, Yanxue; Lin, Mao; Ye, Yongyu; Lin, Jiachen; Zheng, Yu; Liu, Jiaqi; et al. (J Med Genet, 2021)
BACKGROUND: Early-onset scoliosis (EOS), defined by an onset age of scoliosis less than 10 years, conveys significant health risk to affected children. Identification of the molecular aetiology underlying patients with EOS could provide valuable information for both clinical management and prenatal screening. METHODS: In this study, we consecutively recruited a cohort of 447 Chinese patients with operative EOS. We performed exome sequencing (ES) screening on these individuals and their available family members (totaling 670 subjects). Another cohort of 13 patients with idiopathic early-onset scoliosis (IEOS) from the USA who underwent ES was also recruited. RESULTS: After ES data processing and variant interpretation, we detected molecular diagnostic variants in 92 out of 447 (20.6%) Chinese patients with EOS, including 8 patients with molecular confirmation of their clinical diagnosis and 84 patients with molecular diagnoses of previously unrecognised diseases underlying scoliosis. One out of 13 patients with IEOS from the US cohort was molecularly diagnosed. The age at presentation, the number of organ systems involved and the Cobb angle were the three top features predictive of a molecular diagnosis. CONCLUSION: ES enabled the molecular diagnosis/classification of patients with EOS. Specific clinical features/feature pairs are able to indicate the likelihood of gaining a molecular diagnosis through ES.

Perturbations of genes essential for Müllerian duct and Wölffian duct development in Mayer-Rokitansky-Küster-Hauser syndrome. - Chen, Na; Zhao, Sen; Jolly, Angad; Wang, Lianlei; Pan, Hongxin; Yuan, Jian; Chen, Shaoke; Koch, André; Ma, Congcong; Tian, Weijie; Jia, Ziqi; Kang, Jia; et al. (Am J Hum Genet, 2021)
Mayer-Rokitansky-Küster-Hauser syndrome (MRKHS) is associated with congenital absence of the uterus, cervix, and the upper part of the vagina; it is a sex-limited trait. Disrupted development of the Müllerian ducts (MD)/Wölffian ducts (WD) through multifactorial mechanisms has been proposed to underlie MRKHS. In this study, exome sequencing (ES) was performed on a Chinese discovery cohort (442 affected subjects and 941 female control subjects) and a replication MRKHS cohort (150 affected subjects of mixed ethnicity from North America, South America, and Europe). Phenotypic follow-up of the female reproductive system was performed on an additional cohort of PAX8-associated congenital hypothyroidism (CH) (n = 5, Chinese). By analyzing 19 candidate genes essential for MD/WD development, we identified 12 likely gene-disrupting (LGD) variants in 7 genes: PAX8 (n = 4), BMP4 (n = 2), BMP7 (n = 2), TBX6 (n = 1), HOXA10 (n = 1), EMX2 (n = 1), and WNT9B (n = 1), while LGD variants in these genes were not detected in control samples (p = 1.27E-06). Interestingly, a sex-limited penetrance with paternal inheritance was observed in multiple families. One additional PAX8 LGD variant from the replication cohort and two missense variants from both cohorts were revealed to cause loss-of-function of the protein. From the PAX8-associated CH cohort, we identified one individual presenting a syndromic condition characterized by CH and MRKHS (CH-MRKHS). Our study demonstrates the comprehensive utilization of knowledge from developmental biology toward elucidating genetic perturbations, i.e., rare pathogenic alleles involving the same loci, contributing to human birth defects.
Keywords: 46, XX Disorders of Sex Development; Adult; Bone Morphogenetic Protein 4; Bone Morphogenetic Protein 7; Codon, Nonsense; Congenital Abnormalities; Female; Genetic Association Studies; Genetic Pleiotropy; Homeobox A10 Proteins; Homeodomain Proteins; Humans; Mullerian Ducts; Mutation; Paternal Inheritance; PAX8 Transcription Factor; Penetrance; T-Box Domain Proteins; Transcription Factors; Wnt Proteins; Wolffian Ducts

Exome sequencing reveals a novel variant in causing intracranial aneurysm in a Chinese family. - Ding, Xinghuan; Zhao, Sen; Zhang, Qianqian; Yan, Zihui; Wang, Yang; Wu, Yong; Li, Xiaoxin; Liu, Jian; Niu, Yuchen; Zhang, Yisen; Zhang, Mingqi; Wang, Huizi; et al. (J Neurointerv Surg, 2020)
BACKGROUND: Genetic risk factors play an important role in the pathogenesis of familial intracranial aneurysms (FIAs); however, the molecular mechanisms remain largely unknown. OBJECTIVE: To investigate potential FIA-causing genetic variants by rare variant interrogation and a family-based genomics approach in a large family with an extensive multigenerational pedigree with FIAs. METHOD: Exome sequencing (ES) was performed in a dominant likely family with intracranial aneurysms (IAs). Variants were analyzed by an in-house developed pipeline and prioritized using various filtering strategies, including population frequency, variant type, and predicted variant pathogenicity. Sanger sequencing was also performed to evaluate the segregation of the variants with the phenotype. RESULTS: Based on the ES data obtained from five individuals from a family with 7/21 living members affected with IAs, a total of 14 variants were prioritized as candidate variants. Familial segregation analysis revealed that c.2519T>C (p.Leu840Pro) segregated in accordance with Mendelian expectations with the phenotype within the family-that is, present in all IA-affected cases and absent from all unaffected members of the second generation. This missense variant is absent from public databases (1000genome, ExAC, gnomAD, ESP5400), and has damaging predictions by bioinformatics tools (Gerp ++ score = 5.88, CADD score = 16.43, MutationTaster score = 1, LRT score = 0). In addition, 840Leu in NFX1 is robustly conserved in mammals and maps in a region before the RING-type zinc finger domain. CONCLUSION: c.2519T>C (p.Leu840Pro) may contribute to the pathogenetics of a subset of FIAs.
Keywords: Adult; Asian Continental Ancestry Group; Computational Biology; Exome; Female; Genetic Variation; Humans; Intracranial Aneurysm; Male; Middle Aged; Pedigree; Phenotype; Repressor Proteins

Functional biology of the Steel syndrome founder allele and evidence for clan genomics derivation of COL27A1 pathogenic alleles worldwide. - Gonzaga-Jauregui, Claudia; Yesil, Gözde; Nistala, Harikiran; Gezdirici, Alper; Bayram, Yavuz; Nannuru, Kalyan C; Pehlivan, Davut; Yuan, Bo; Jimenez, Johanna; Sahin, Yavuz; Paine, Ingrid S; Akdemir, Zeynep Coban; et al. (Eur J Hum Genet, 2020)
Previously we reported the identification of a homozygous COL27A1 (c.2089G>C; p.Gly697Arg) missense variant and proposed it as a founder allele in Puerto Rico segregating with Steel syndrome (STLS, MIM #615155); a rare osteochondrodysplasia characterized by short stature, congenital bilateral hip dysplasia, carpal coalitions, and scoliosis. We now report segregation of this variant in five probands from the initial clinical report defining the syndrome and an additional family of Puerto Rican descent with multiple affected adult individuals. We modeled the orthologous variant in murine Col27a1 and found it recapitulates some of the major Steel syndrome associated skeletal features including reduced body length, scoliosis, and a more rounded skull shape. Characterization of the in vivo murine model shows abnormal collagen deposition in the extracellular matrix and disorganization of the proliferative zone of the growth plate. We report additional COL27A1 pathogenic variant alleles identified in unrelated consanguineous Turkish kindreds suggesting Clan Genomics and identity-by-descent homozygosity contributing to disease in this population. The hypothesis that carrier states for this autosomal recessive osteochondrodysplasia may contribute to common complex traits is further explored in a large clinical population cohort. Our findings augment our understanding of COL27A1 biology and its role in skeletal development; and expand the functional allelic architecture in this gene underlying both rare and common disease phenotypes.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Bone Development; Child; Child, Preschool; Consanguinity; Extracellular Matrix; Female; Fibrillar Collagens; Founder Effect; Gene Frequency; Hip Dislocation; Homozygote; Humans; Male; Mice; Mice, Inbred C57BL; Mutation; Pedigree; Scoliosis; Syndrome

Genetic and molecular mechanism for distinct clinical phenotypes conveyed by allelic truncating mutations implicated in FBN1. - Lin, Mao; Liu, Zhenlei; Liu, Gang; Zhao, Sen; Li, Chao; Chen, Weisheng; Coban Akdemir, Zeynep; Lin, Jiachen; Song, Xiaofei; Wang, Shengru; Xu, Qiming; Zhao, Yanxue; et al. (Mol Genet Genomic Med, 2020)
BACKGROUND: The molecular and genetic mechanisms by which different single nucleotide variant alleles in specific genes, or at the same genetic locus, cause distinct disease phenotypes often remain unclear. Allelic truncating mutations of FBN1 could cause either classical Marfan syndrome (MFS) or a more complicated phenotype associated with Marfanoid-progeroid-lipodystrophy syndrome (MPLS). METHODS: We investigated a small cohort, encompassing two classical MFS and one MPLS subjects from China, whose clinical presentation included scoliosis potentially requiring surgical intervention. Targeted next generation sequencing was performed on all the participants. We analyzed the molecular diagnosis, clinical features, and the potential molecular mechanism involved in the MPLS subject in our cohort. RESULTS: We report a novel de novo FBN1 mutation for the first Chinese subject with MPLS, a more complicated fibrillinopathy, and two subjects with more classical MFS. We further predict that the MPLS truncating mutation, and others previously reported, is prone to escape the nonsense-mediated decay (NMD), while MFS mutations are predicted to be subjected to NMD. Also, the MPLS mutation occurs within the glucogenic hormone asprosin domain of FBN1. In vitro experiments showed that the single MPLS mutation p.Glu2759Cysfs*9 appears to perturb proper FBN1 protein aggregation as compared with the classical MFS mutation p.Tyr2596Thrfs*86. Both mutations appear to upregulate SMAD2 phosphorylation in vitro. CONCLUSION: We provide direct evidence that a dominant-negative interaction of FBN1 potentially explains the complex MPLS phenotypes through genetic and functional analysis. Our study expands the mutation spectrum of FBN1 and highlights the potential molecular mechanism for MPLS.
Keywords: Adolescent; Adult; Child; Female; Fibrillin-1; HEK293 Cells; Humans; Lipodystrophy; Marfan Syndrome; Mutation; Phenotype; Progeria; Protein Domains; Smad2 Protein

Human and mouse studies establish TBX6 in Mendelian CAKUT and as a potential driver of kidney defects associated with the 16p11.2 microdeletion syndrome. - Yang, Nan; Wu, Nan; Dong, Shuangshuang; Zhang, Ling; Zhao, Yanxue; Chen, Weisheng; Du, Renqian; Song, Chengcheng; Ren, Xiaojun; Liu, Jiaqi; Pehlivan, Davut; Liu, Zhenlei; et al. (Kidney Int, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUTs) are the most common cause of chronic kidney disease in children. Human 16p11.2 deletions have been associated with CAKUT, but the responsible molecular mechanism remains to be illuminated. To explore this, we investigated 102 carriers of 16p11.2 deletion from multi-center cohorts, among which we retrospectively ascertained kidney morphologic and functional data from 37 individuals (12 Chinese and 25 Caucasian/Hispanic). Significantly higher CAKUT rates were observed in 16p11.2 deletion carriers (about 25% in Chinese and 16% in Caucasian/Hispanic) than those found in the non-clinically ascertained general populations (about 1/1000 found at autopsy). Furthermore, we identified seven additional individuals with heterozygous loss-of-function variants in TBX6, a gene that maps to the 16p11.2 region. Four of these seven cases showed obvious CAKUT. To further investigate the role of TBX6 in kidney development, we engineered mice with mutated Tbx6 alleles. The Tbx6 heterozygous null (i.e., loss-of-function) mutant (Tbx6) resulted in 13% solitary kidneys. Remarkably, this incidence increased to 29% in a compound heterozygous model (Tbx6) that reduced Tbx6 gene dosage to below haploinsufficiency, by combining the null allele with a novel mild hypomorphic allele (mh). Renal hypoplasia was also frequently observed in these Tbx6-mutated mouse models. Thus, our findings in patients and mice establish TBX6 as a novel gene involved in CAKUT and its gene dosage insufficiency as a potential driver for kidney defects observed in the 16p11.2 microdeletion syndrome.

Increased gene dosages induce congenital cervical vertebral malformations in humans and mice. - Ren, Xiaojun; Yang, Nan; Wu, Nan; Xu, Ximing; Chen, Weisheng; Zhang, Ling; Li, Yingping; Du, Ren-Qian; Dong, Shuangshuang; Zhao, Sen; Chen, Shuxia; Jiang, Li-Ping; et al. (J Med Genet, 2020)
BACKGROUND: Congenital vertebral malformations (CVMs) manifest with abnormal vertebral morphology. Genetic factors have been implicated in CVM pathogenesis, but the underlying pathogenic mechanisms remain unclear in most subjects. We previously reported that the human 16p11.2 BP4-BP5 deletion and its associated dosage reduction caused CVMs. We aim to investigate the reciprocal 16p11.2 BP4-BP5 duplication and its potential genetic contributions to CVMs. METHODS AND RESULTS: Patients who were found to carry the 16p11.2 BP4-BP5 duplication by chromosomal microarray analysis were retrospectively analysed for their vertebral phenotypes. The spinal assessments in seven duplication carriers showed that four (57%) presented characteristics of CVMs, supporting the contention that increased dosage could induce CVMs. For further in vivo functional investigation in a model organism, we conducted genome editing of the upstream regulatory region of mouse using CRISPR-Cas9 and obtained three mouse mutant alleles ( to ) with elevated expression levels of . Luciferase reporter assays showed that the allele presented with the 160% expression level of that observed in the reference (+) allele. Therefore, the homozygous mice could functionally mimic the dosage of heterozygous carriers of 16p11.2 BP4-BP5 duplication (approximately 150%, ie, 3/2 gene dosage of the normal level). Remarkably, 60% of the mice manifested with CVMs. Consistent with our observations in humans, the CVMs induced by increased dosage in mice mainly affected the cervical vertebrae. CONCLUSION: Our findings in humans and mice consistently support that an increased dosage contributes to the risk of developing cervical CVMs.

KIAA1217: A novel candidate gene associated with isolated and syndromic vertebral malformations. - Al Dhaheri, Noura; Wu, Nan; Zhao, Sen; Wu, Zhihong; Blank, Robert D; Zhang, Jianguo; Raggio, Cathy; Halanski, Matthew; Shen, Jianxiong; Noonan, Ken; Qiu, Guixing; Nemeth, Blaise; et al. (Am J Med Genet A, 2020)
Vertebral malformations (VMs) are caused by alterations in somitogenesis and may occur in association with other congenital anomalies. The genetic etiology of most VMs remains unknown and their identification may facilitate the development of novel therapeutic and prevention strategies. Exome sequencing was performed on both the discovery cohort of nine unrelated probands from the USA with VMs and the replication cohort from China (Deciphering Disorders Involving Scoliosis & COmorbidities study). The discovery cohort was analyzed using the PhenoDB analysis tool. Heterozygous and homozygous, rare and functional variants were selected and evaluated for their ClinVar, HGMD, OMIM, GWAS, mouse model phenotypes, and other annotations to identify the best candidates. Genes with candidate variants in three or more probands were selected. The replication cohort was analyzed by another in-house developed pipeline. We identified rare heterozygous variants in KIAA1217 in four out of nine probands in the discovery cohort and in five out of 35 probands in the replication cohort. Collectively, we identified 11 KIAA1217 rare variants in 10 probands, three of which have not been described in gnomAD and one of which is a nonsense variant. We propose that genetic variations of KIAA1217 may contribute to the etiology of VMs.
Keywords: Adolescent; Cervical Vertebrae; Child; Codon, Nonsense; Databases, Genetic; Female; Heterozygote; Homozygote; Humans; Male; Proteins; Spinal Diseases; Thoracic Vertebrae

TBX6 missense variants expand the mutational spectrum in a non-Mendelian inheritance disease. - Chen, Weisheng; Lin, Jiachen; Wang, Lianlei; Li, Xiaoxin; Zhao, Sen; Liu, Jiaqi; Akdemir, Zeynep C; Zhao, Yanxue; Du, Renqian; Ye, Yongyu; Song, Xiaofei; Zhang, Yuanqiang; et al. (Hum Mutat, 2020)
Congenital scoliosis (CS) is a birth defect with variable clinical and anatomical manifestations due to spinal malformation. The genetic etiology underlying about 10% of CS cases in the Chinese population is compound inheritance by which the gene dosage is reduced below that of haploinsufficiency. In this genetic model, the trait manifests as a result of the combined effect of a rare variant and common pathogenic variant allele at a locus. From exome sequencing (ES) data of 523 patients in Asia and two patients in Texas, we identified six TBX6 gene-disruptive variants from 11 unrelated CS patients via ES and in vitro functional testing. The in trans mild hypomorphic allele was identified in 10 of the 11 subjects; as anticipated these 10 shared a similar spinal deformity of hemivertebrae. The remaining case has a homozygous variant in TBX6 (c.418C>T) and presents a more severe spinal deformity phenotype. We found decreased transcriptional activity and abnormal cellular localization as the molecular mechanisms for TBX6 missense loss-of-function alleles. Expanding the mutational spectrum of TBX6 pathogenic alleles enabled an increased molecular diagnostic detection rate, provided further evidence for the gene dosage-dependent genetic model underlying CS, and refined clinical classification.
Keywords: Alleles; Cell Line; Female; Gene Expression; Genes, Reporter; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Inheritance Patterns; Male; Models, Molecular; Molecular Diagnostic Techniques; Mutation, Missense; Phenotype; Protein Conformation; Radiography; Sequence Analysis, DNA; Spine; Structure-Activity Relationship; T-Box Domain Proteins; Whole Exome Sequencing

Insights into genetics, human biology and disease gleaned from family based genomic studies. - Posey, Jennifer E; O'Donnell-Luria, Anne H; Chong, Jessica X; Harel, Tamar; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Buyske, Steven; Pehlivan, Davut; Carvalho, Claudia M B; Baxter, Samantha; Sobreira, Nara; Liu, Pengfei; et al. (Genet Med, 2019)
Identifying genes and variants contributing to rare disease phenotypes and Mendelian conditions informs biology and medicine, yet potential phenotypic consequences for variation of >75% of the ~20,000 annotated genes in the human genome are lacking. Technical advances to assess rare variation genome-wide, particularly exome sequencing (ES), enabled establishment in the United States of the National Institutes of Health (NIH)-supported Centers for Mendelian Genomics (CMGs) and have facilitated collaborative studies resulting in novel "disease gene" discoveries. Pedigree-based genomic studies and rare variant analyses in families with suspected Mendelian conditions have led to the elucidation of hundreds of novel disease genes and highlighted the impact of de novo mutational events, somatic variation underlying nononcologic traits, incompletely penetrant alleles, phenotypes with high locus heterogeneity, and multilocus pathogenic variation. Herein, we highlight CMG collaborative discoveries that have contributed to understanding both rare and common diseases and discuss opportunities for future discovery in single-locus Mendelian disorder genomics. Phenotypic annotation of all human genes; development of bioinformatic tools and analytic methods; exploration of non-Mendelian modes of inheritance including reduced penetrance, multilocus variation, and oligogenic inheritance; construction of allelic series at a locus; enhanced data sharing worldwide; and integration with clinical genomics are explored. Realizing the full contribution of rare disease research to functional annotation of the human genome, and further illuminating human biology and health, will lay the foundation for the Precision Medicine Initiative.
Keywords: Databases, Genetic; Genetic Diseases, Inborn; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; National Institutes of Health (U.S.); Pedigree; United States; Whole Exome Sequencing

Reanalysis of Clinical Exome Sequencing Data. - Liu, Pengfei; Meng, Linyan; Normand, Elizabeth A; Xia, Fan; Song, Xiaofei; Ghazi, Andrew; Rosenfeld, Jill; Magoulas, Pilar L; Braxton, Alicia; Ward, Patricia; Dai, Hongzheng; Yuan, Bo; et al. (N Engl J Med, 2019)
Keywords: Exome; Genetic Diseases, Inborn; Genetic Testing; Humans; Mutation; Phenotype; Sequence Analysis, DNA; Whole Exome Sequencing

TBX6 compound inheritance leads to congenital vertebral malformations in humans and mice. - Yang, Nan; Wu, Nan; Zhang, Ling; Zhao, Yanxue; Liu, Jiaqi; Liang, Xiangyu; Ren, Xiaojun; Li, Weiyu; Chen, Weisheng; Dong, Shuangshuang; Zhao, Sen; Lin, Jiachen; et al. (Hum Mol Genet, 2019)
Congenital vertebral malformations (CVMs) are associated with human TBX6 compound inheritance that combines a rare null allele and a common hypomorphic allele at the TBX6 locus. Our previous in vitro evidence suggested that this compound inheritance resulted in a TBX6 gene dosage of less than haploinsufficiency (i.e. <50%) as a potential mechanism of TBX6-associated CVMs. To further investigate this pathogenetic model, we ascertained and collected 108 Chinese CVM cases and found that 10 (9.3%) of them carried TBX6 null mutations in combination with common hypomorphic variants at the second TBX6 allele. For in vivo functional verification and genetic analysis of TBX6 compound inheritance, we generated both null and hypomorphic mutations in mouse Tbx6 using the CRISPR-Cas9 method. These Tbx6 mutants are not identical to the patient variants at the DNA sequence level, but instead functionally mimic disease-associated TBX6 variants. Intriguingly, as anticipated by the compound inheritance model, a high penetrance of CVM phenotype was only observed in the mice with combined null and hypomorphic alleles of Tbx6. These findings are consistent with our experimental observations in humans and supported the dosage effect of TBX6 in CVM etiology. In conclusion, our findings in the newly collected human CVM subjects and Tbx6 mouse models consistently support the contention that TBX6 compound inheritance causes CVMs, potentially via a gene dosage-dependent mechanism. Furthermore, mouse Tbx6 mutants mimicking human CVM-associated variants will be useful models for further mechanistic investigations of CVM pathogenesis in the cases associated with TBX6.
Keywords: Adolescent; Alleles; Animals; Child; Child, Preschool; Congenital Abnormalities; CRISPR-Cas Systems; Disease Models, Animal; Female; Haploinsufficiency; Humans; Infant; Male; Mice; Mutation; Phenotype; Scoliosis; Spine; T-Box Domain Proteins

TBX6-associated congenital scoliosis (TACS) as a clinically distinguishable subtype of congenital scoliosis: further evidence supporting the compound inheritance and TBX6 gene dosage model. - Liu, Jiaqi; Wu, Nan; Yang, Nan; Takeda, Kazuki; Chen, Weisheng; Li, Weiyu; Du, Renqian; Liu, Sen; Zhou, Yangzhong; Zhang, Ling; Liu, Zhenlei; Zuo, Yuzhi; et al. (Genet Med, 2019)
PURPOSE: To characterize clinically measurable endophenotypes, implicating the TBX6 compound inheritance model. METHODS: Patients with congenital scoliosis (CS) from China(N = 345, cohort 1), Japan (N = 142, cohort 2), and the United States (N = 10, cohort 3) were studied. Clinically measurable endophenotypes were compared according to the TBX6 genotypes. A mouse model for Tbx6 compound inheritance (N = 52) was investigated by micro computed tomography (micro-CT). A clinical diagnostic algorithm (TACScore) was developed to assist in clinical recognition of TBX6-associated CS (TACS). RESULTS: In cohort 1, TACS patients (N = 33) were significantly younger at onset than the remaining CS patients (P = 0.02), presented with one or more hemivertebrae/butterfly vertebrae (P = 4.9 × 10), and exhibited vertebral malformations involving the lower part of the spine (T8-S5, P = 4.4 × 10); observations were confirmed in two replication cohorts. Simple rib anomalies were prevalent in TACS patients (P = 3.1 × 10), while intraspinal anomalies were uncommon (P = 7.0 × 10). A clinically usable TACScore was developed with an area under the curve (AUC) of 0.9 (P = 1.6 × 10). A Tbx6 mouse model supported that a gene dosage effect underlies the TACS phenotype. CONCLUSION: TACS is a clinically distinguishable entity with consistent clinically measurable endophenotypes. The type and distribution of vertebral column abnormalities in TBX6/Tbx6 compound inheritance implicate subtle perturbations in gene dosage as a cause of spine developmental birth defects responsible for about 10% of CS.

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease. - Liu, Jiaqi; Zhou, Yangzhong; Liu, Sen; Song, Xiaofei; Yang, Xin-Zhuang; Fan, Yanhui; Chen, Weisheng; Akdemir, Zeynep Coban; Yan, Zihui; Zuo, Yuzhi; Du, Renqian; Liu, Zhenlei; et al. (Hum Genet, 2018)
With the recent advance in genome-wide association studies (GWAS), disease-associated single nucleotide polymorphisms (SNPs) and copy number variants (CNVs) have been extensively reported. Accordingly, the issue of incorrect identification of recombination events that can induce the distortion of multi-allelic or hemizygous variants has received more attention. However, the potential distorted calculation bias or significance of a detected association in a GWAS due to the coexistence of CNVs and SNPs in the same genomic region may remain under-recognized. Here we performed the association study within a congenital scoliosis (CS) cohort whose genetic etiology was recently elucidated as a compound inheritance model, including mostly one rare variant deletion CNV null allele and one common variant non-coding hypomorphic haplotype of the TBX6 gene. We demonstrated that the existence of a deletion in TBX6 led to an overestimation of the contribution of the SNPs on the hypomorphic allele. Furthermore, we generalized a model to explain the calculation bias, or distorted significance calculation for an association study, that can be 'induced' by CNVs at a locus. Meanwhile, overlapping between the disease-associated SNPs from published GWAS and common CNVs (overlap 10%) and pathogenic/likely pathogenic CNVs (overlap 99.69%) was significantly higher than the random distribution (p < 1 × 10 and p = 0.034, respectively), indicating that such co-existence of CNV and SNV alleles might generally influence data interpretation and potential outcomes of a GWAS. We also verified and assessed the influence of colocalizing CNVs to the detection sensitivity of disease-associated SNP variant alleles in another adolescent idiopathic scoliosis (AIS) genome-wide association study. We proposed that detecting co-existent CNVs when evaluating the association signals between SNPs and disease traits could improve genetic model analyses and better integrate GWAS with robust Mendelian principles.
Keywords: Adolescent; Congenital Abnormalities; DNA Copy Number Variations; Female; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genomics; Genotype; Haplotypes; Humans; Phenotype; Polymorphism, Single Nucleotide; Scoliosis

Identification of likely pathogenic and known variants in TSPEAR, LAMB3, BCOR, and WNT10A in four Turkish families with tooth agenesis. - Du, Renqian; Dinckan, Nuriye; Song, Xiaofei; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Guven, Yeliz; Aktoren, Oya; Kayserili, Hülya; Petty, Lauren E; Muzny, Donna M; Below, Jennifer E; Boerwinkle, Eric; et al. (Hum Genet, 2018)
Tooth agenesis (TA), the failure of development of one or more permanent teeth, is a common craniofacial abnormality observed in different world populations. The genetic etiology of TA is heterogeneous; more than a dozen genes have been associated with isolated or nonsyndromic TA, and more than 80 genes with syndromic forms. In this study, we applied whole exome sequencing (WES) to identify candidate genes contributing to TA in four Turkish families. Likely pathogenic variants with a low allele frequency in the general population were identified in four disease-associated genes, including two distinct variants in TSPEAR, associated with syndromic and isolated TA in one family each; a variant in LAMB3 associated with syndromic TA in one family; and a variant in BCOR plus a disease-associated WNT10A variant in one family with syndromic TA. With the notable exception of WNT10A (Tooth agenesis, selective, 4, MIM #150400), the genotype-phenotype relationships described in the present cohort represent an expansion of the clinical spectrum associated with these genes: TSPEAR (Deafness, autosomal recessive 98, MIM #614861), LAMB3 (Amelogenesis imperfecta, type IA, MIM #104530; Epidermolysis bullosa, junctional, MIMs #226700 and #226650), and BCOR (Microphthalmia, syndromic 2, MIM #300166). We provide evidence supporting the candidacy of these genes with TA, and propose TSPEAR as a novel nonsyndromic TA gene. Our data also suggest potential multilocus genomic variation, or mutational burden, in a single family, involving the BCOR and WNT10A loci, underscoring the complexity of the genotype-phenotype relationship in the common complex trait of TA.
Keywords: Anodontia; Cell Adhesion Molecules; Child; Child, Preschool; Female; Genetic Markers; Humans; Male; Mutation; Pedigree; Phenotype; Proteins; Proto-Oncogene Proteins; Repressor Proteins; Turkey; Wnt Proteins

Perturbations of BMP/TGF-β and VEGF/VEGFR signalling pathways in non-syndromic sporadic brain arteriovenous malformations (BAVM). - Wang, Kun; Zhao, Sen; Liu, Bowen; Zhang, Qianqian; Li, Yaqi; Liu, Jiaqi; Shen, Yan; Ding, Xinghuan; Lin, Jiachen; Wu, Yong; Yan, Zihui; Chen, Jia; et al. (J Med Genet, 2018)
BACKGROUND: Brain arteriovenous malformations (BAVM) represent a congenital anomaly of the cerebral vessels with a prevalence of 10-18/100 000. BAVM is the leading aetiology of intracranial haemorrhage in children. Our objective was to identify gene variants potentially contributing to disease and to better define the molecular aetiology underlying non-syndromic sporadic BAVM. METHODS: We performed whole-exome trio sequencing of 100 unrelated families with a clinically uniform BAVM phenotype. Pathogenic variants were then studied in vivo using a transgenic zebrafish model. RESULTS: We identified four pathogenic heterozygous variants in four patients, including one in the established BAVM-related gene, , and three damaging variants in novel candidate genes: , and , which we then functionally validated in zebrafish. In addition, eight likely pathogenic heterozygous variants (, and ) were identified in eight patients, and 16 patients carried one or more variants of uncertain significance. Potential oligogenic inheritance ( with , with and with ) was identified in three patients. Regulation of sma- and mad-related proteins (SMADs) (involved in bone morphogenic protein (BMP)/transforming growth factor beta (TGF-β) signalling) and vascular endothelial growth factor (VEGF)/vascular endotheliual growth factor recepter 2 (VEGFR2) binding and activity (affecting the VEGF signalling pathway) were the most significantly affected biological process involved in the pathogenesis of BAVM. CONCLUSIONS: Our study highlights the specific role of BMP/TGF-β and VEGF/VEGFR signalling in the aetiology of BAVM and the efficiency of intensive parallel sequencing in the challenging context of genetically heterogeneous paradigm.